Terapia comportamental cognitiva para pessoas com transtorno bipolar Cognitive behavioral therapy for bipolar disorders - Francisco Lotufo Neto (Brazilian Journal of Psychiatry, 2004)
Descrição dos objetivos e principais técnicas da terapia comportamental cognitiva usadas para a psicoterapia das pessoas com transtorno bipolar. Objectives and main techniques of cognitive behavior therapy for the treatment of bipolar disorder patients are described.